Influence of conductive and semi-conductive nanoparticles on the dielectric response of natural ester-based nanofluid insulation - Mohamad Zul Hilmey Makmud; H. A. Illias; C. Y. Chee; Mohd Sani Sarjadi (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Nowadays, studies of alternative liquid insulation in high voltage apparatus have become increasingly important due to higher concerns regarding safety, sustainable resources and environmentally friendly issues. To fulfil this demand, natural ester has been extensively studied and it can become a potential product to replace mineral oil in power transformers. In addition, the incorporation of nanoparticles has been remarkable in producing improved characteristics of insulating oil. Although much extensive research has been carried out, there is no general agreement on the influence on the dielectric response of base oil due to the addition of different amounts and conductivity types of nanoparticle concentrations. Therefore, in this work, a natural ester-based nanofluid was prepared by a two-step method using iron oxide (Fe2O3) and titanium dioxide (TiO2) as the conductive and semi-conductive nanoparticles, respectively. The concentration amount of each nanoparticle types was varied at 0.01, 0.1 and 1.0 g/L. The nanofluid samples were characterised by visual inspection, morphology and the dynamic light scattering (DLS) method before the dielectric response measurement was carried out for frequency-dependent spectroscopy (FDS), current-voltage (I-V), and dielectric breakdown (BD) strength. The results show that the dielectric spectra and I-V curves of nanofluid-based iron oxide increases with the increase of iron oxide nanoparticle loading, while for titanium dioxide, it exhibits a decreasing response. The dielectric BD strength is enhanced for both types of nanoparticles at 0.01 g/L concentration. However, the increasing amount of nanoparticles at 0.1 and 1.0 g/L led to a contrary dielectric BD response. Thus, the results indicate that the augmentation of conductive nanoparticles in the suspension can lead to overlapping mechanisms. Consequently, this reduces the BD strength compared to pristine materials during electron injection in high electric fields.